MODERNISASI DAN GAYA HIDUP - Wahyuni Husain (IAIN Palopo, 2009)
Modernization is a continuous process that have been lasting beyond the time. It effort the various product like a life pattern, culture, life style, and many other aspects. The existence of modernism is not only to supply ease for human being, but also to create a bad, impact which is more prominent, such as the appearance of consumerism among the society due to the economic development which move more globally. The characteristics of such an appearance are seen at the preference over the west culture, instant life style, consumerism that is eventually deteriorated by a hedonism.